'The Spirit is a bone' – Masculinity, authority, and ideology. Issue 2 (3rd April 2022) - McSherry, Tony
ABSTRACT: This article is a phenomenology of masculinity, leading into questions of authority and ideology. Phenomenology draws on one's experience, which includes here the author's experience of being drawn to thinkers in the phenomenological and (psycho)analytical traditions, such as Levinas, Freud, Husserl, Heidegger, and Lacan. Recognition is regarded as the key to becoming what we are, in a complex 'thrownness' which we cannot escape. It appears that coming to know one's masculinity (and femininity) is part of this becoming; some things do not change, expressing the inert quality (Hegelian bone-like) and repetitiveness of ideology. Recognition is dependent on who has the authority to recognise the other, and this is explored in terms of the therapist's authority. The importance of openness to the other person, and oneself as a therapist, is seen as crucial in allowing a space for a discovery of embodied meanings. But a longstanding dominant ideology of scientism has led to alienation from such embodiment, and one reaction to this may be an appeal to a kind of authoritarian certainty in politics. Ultimately, we only have ourselves in what appears to be an urgent struggle for free speech in therapies, and in the world.